Detection of Toxoplasma gondii Infection in Rodents, Shrews and Cats in Unguja Island, Zanzibar - Cynthia M. Paul; Ally A. Ally; Ernatus M. Mkupasi; Martin J. Martin; Abdul A.S. Katakweba (Universitas Airlangga, 2024)
Background: Toxoplasma gondii is an intracellular protozoan parasite that causes a zoonotic infection known as toxoplasmosis. Felid vertebrates including cats serve as the definitive hosts of T. gondii and rodents and shrews are among the common intermediate and reservoir hosts. Little is known about the infection in both humans and animals despite the high interaction between humans and cats on the island. Purpose: This study aimed at determining the prevalence of T. gondii infection in rodents, shrews and cats in Unguja Island, Zanzibar. Method: The study employed a cross-sectional design. A total of 366 small mammals (230 rodents, 43 shrews and 93 cats) were captured and blood was sampled from the seven districts of Unguja Island. Serum samples were subjected to the Indirect ELISA technique with the aid of the ID Screen® Toxoplasmosis Indirect Multi-species Kit to look for antibodies directed against T. gondii. Results: Seropositive samples were detected from one rodent species (Rattus rattus) and one shrew species (Crocidura spp.) among the six different rodent and shrew species captured. Fifty-one seropositive samples from cats were detected where eight were from pet cats and 43 from stray cats. In rodents, no significant variation was found according to species, sex and habitat (p≥0.05) but in cats, there was a significant variation between habitats (p≤0.05). Conclusion: The study revealed the exposure status of rodents, shrews and both stray and pet cats in Unguja Island, thereby revealing the potential risk of the infection transmission to humans due to close proximity with these animals, especially cats as pets. Emphasis should be made through public health education programs about the transmission of the infection and the control measures needed to mitigate the risks.